Pengaruh Kualitas Kehidupan Kerja dan Keseimbangan Kehidupan Kerja Terhadap Performa Karyawan: Peran Mediasi Kepuasan Kerja - Bayu Widhi Respati; Muhammad Ihwanudin; Masmira Kurniawati (Jurnal Manajerial, 2023)
Background – The relationship between work and personal life has been the subject of research of interest to academics and practitioners at the moment. Job conditions, work patterns, and demands have been drivers of reform, changes in demographic composition, and labor market evolution. The number of working hours, methods of regulating working hours, as well as the availability of rest periods significantly affect the quality of work and workers' lives. The phenomenon of Great Resignation has also increased after the Covid-19 pandemic as an indication that the issue of work-life balance is the main discussion of social and labor market problems. Environmental adjustments and flexibility of working hours are considered capable of driving current business performance . Aim – The purpose of this research is to determine the effect of quality of work life and work-life balance on employee performance with job satisfaction as a moderation variable. Design/ Methodology/ Approach – This research uses a quantitative approach with survey methods to obtain data from respondents. Findings – The results of this research show that the quality of work life and work-life balance have a positive and significant effect on job satisfaction and employee performance. While the direct relationship between job satisfaction and job performance did not have a significant effect, so the role of mediating variables of job satisfaction did not occur. These results show that employees do not enjoy good job satisfaction, but the impact does not motivate employees to contribute more to their work. This is very bad because employees are not motivated to develop and maximize work performance. The results of this study are expected to provide input for companies to improve the quality of work life and work-life balance of employees so as to improve the work performance of employees. Its employees will therefore be compressed on the company’s overall productivity. Conclusion – Stakeholders must pay attention to quality of work life and work-life balance to maintain job satisfaction and ultimately promote sustainable employee performance. Research Implications – This research recommends developing a conceptual framework by adding stress, burnout, remuneration, and work from home factors in the digital age. Limitations of Research – This research is only limited to the point of view of the woman, not to include the point of view of the organization.